The radical induced cell death protein 1 (RCD1) supports transcriptional activation of genes for chloroplast antioxidant enzymes - Hiltscher, Heiko; Rudnik, Radoslaw; Shaikhali, Jehad; Heiber, Isabelle; Mellenthin, Marina; Meirelles Duarte, Iuri; Schuster, Günter; Kahmann, Uwe; Baier, Margarete (Frontiers in Plant Science, 2014)
The rimb1 (redox imbalanced 1) mutation was mapped to the RCD1 locus (radical-induced cell death 1; At1g32230) demonstrating that a major factor involved in redox-regulation genes for chloroplast antioxidant enzymes and protection against photooxidative stress, RIMB1, is identical to the regulator of disease response reactions and cell death, RCD1. Discovering this link let to our investigation of its regulatory mechanism. We show in yeast that RCD1 can physically interact with the transcription factor Rap2.4a which provides redox-sensitivity to nuclear expression of genes for chloroplast antioxidant enzymes. In the rimb1 (rcd1-6) mutant a single nucleotide exchange results in a truncated RCD1 protein lacking the transcription factor binding site. Protein-protein interaction between full-length RCD1 and Rap2.4a is supported by H2O2, but not sensitive to the antioxidants dithiotreitol and ascorbate. In combination with transcript abundance analysis in Arabidopsis, it is concluded that RCD1 stabilizes the Rap2.4-dependent redox-regulation of the genes encoding chloroplast antioxidant enzymes in a widely redox-independent manner. Over the years, rcd1-mutant alleles have been described to develop symptoms like chlorosis, lesions along the leaf rims and in the mesophyll and (secondary) induction of extra- and intra-plastidic antioxidant defense mechanisms. All these rcd1 mutant characteristics were observed in rcd1-6 to succeed low activation of the chloroplast antioxidant system and glutathione biosynthesis. We conclude that RCD1 protects plant cells from running into ROS (reactive oxygen species)-triggered programs, such as cell death and activation of pathogen-responsive genes (PR genes) and extra-plastidic antioxidant enzymes, by supporting the induction of the chloroplast antioxidant system.